2018
DOI: 10.7566/jpsj.87.014705
|View full text |Cite
|
Sign up to set email alerts
|

Fermi Surface, Pressure-Induced Antiferromagnetic Order, and Superconductivity in FeSe

Abstract: The pressure dependence of the structural (Ts), antiferromagnetic (Tm), and superconducting (Tc) transition temperatures in FeSe is investigated on the basis of the 16-band d-p model. At ambient pressure, a shallow hole pocket disappears due to the correlation effect, as observed in the angular-resolved photoemission spectroscopy (ARPES) and quantum oscillation (QO) experiments, resulting in the suppression of the antiferromagnetic order, in contrast to the other iron pnictides. The orbital-polarization intera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 67 publications
3
8
0
Order By: Relevance
“…However, electronic interactions and associated self-energy effects are known to be important in FeSe, constituting an example of a Hund's metal [25]. Important properties of Hund's metals include the existence of orbital dependent mass renormalizations [43][44][45], and an associated redistribution of the relative importance of different orbital dependent scattering channels in the spin susceptibility [46].…”
mentioning
confidence: 99%
“…However, electronic interactions and associated self-energy effects are known to be important in FeSe, constituting an example of a Hund's metal [25]. Important properties of Hund's metals include the existence of orbital dependent mass renormalizations [43][44][45], and an associated redistribution of the relative importance of different orbital dependent scattering channels in the spin susceptibility [46].…”
mentioning
confidence: 99%
“…These small FSs and the lowenergy bandstructure have not still been reproduced by the density-functional theory (DFT) [37], DFT+U [38], the dynamical mean field theory (DMFT) [18][19][20]39] and quasiparticle self-consistent GW (QSGW ) [40]. Several studies based on adjusted models to reproduce the low-energy bands of angle resolved photoemission spectroscopy (ARPES) [31] can explain the enhancement of orbital and magnetic fluctuations in T -P phase [41][42][43].…”
mentioning
confidence: 99%
“…We confirmed that the geometric term is dominant in this region. To reproduce the Fermi surfaces of FeSe observed in experiments, we slightly modify the hopping parameters given by the first-principles calculation 68,78,79 . For this purpose, the energies of the d xy -orbital band and the d xz/yz -orbital band are shifted by (−0.28, 0, 0.20) and (−0.27, 0, 0.13) at (Γ,X,M ) points in the folded Brillouin zone, respectively.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…To reproduce the experimentally observed Fermi surfaces of FeSe, we take into account additional hopping parameters in addition to those given by the WIEN2k code, in a similar manner to Refs. 68,78,79 (see Appendix. C for details).…”
Section: B Fesementioning
confidence: 99%